Entrepreneurial leadership, organisational creativity, and firm performance in Chinese SMEs context - Wu, Chendong (2016)
Researchers have identified a wide range of factors that affect organisational creativity. The leadership behaviour of top managers is one of the most important. However, few studies have empirically examined the relationship between the leadership behaviour of these leaders and creativity at the organisational level. In this study, a style of leadership labelled “entrepreneurial” is considered in the context of Chinese SMEs, by considering its potential to create an environment in which creative activities can flourish. The entrepreneurial leader is central to the enterprise, creating visionary scenarios and facilitating a group of capable members to enact their vision, further fostering organisational creativity. As organisational creativity is important for business success, there is a significant need for research into the impact of entrepreneurial leadership.